The Topicality of Historiosophy - Kieliszek, Zdzisław (Studia Warmińskie, 2013)
In this paper the author discusses the problem of researching the sense of human history and laws which govern it. The paper has four parts. In the first the author briefly outlines the historiosophical issues. The second part of the article is devoted to the most important reproaches that in contemporary philosophical discourses are extended to historiosophic thinking. The author briefly discusses the five grounds: 1) There are no reasons for developing the historiosophical tradition; 2) Complete unpredictability of history; 3) Excessive catastrophism of the historiosophic thinking; 4) A-historical attitude of modern man; 5) There is no a-historic, uniform and constant frame of reference for the historical process. In the third installment these objections are rebutted. Their major weaknesses and counter-arguments are identified. In the last paragraph the author summarizes the analysis. He also comes to the conclusion that the historiosophical issue is still valid, and it is imporatant for theoretical and practical reasons.